An overview of international literature from cystic fibrosis registries. Part 5: Update 2012–2015 on lung disease. Issue 11 (10th May 2016) - Salvatore, Donatello; Buzzetti, Roberto; Mastella, Gianni
Summary: Patient registry data is a tool for defining the clinical course and risk factors in patients with less common diseases like Cystic Fibrosis. Forty‐one registry‐based reports on lung disease in Cystic Fibrosis were published between 2011 and 2015. The aim of this review is to describe and discuss the results of these reports, focusing on the risk factors for lung disease progression, specific microbiologic pathogens (e.g., non‐tuberculous mycobacteria), disease complications, comparisons between registries of different countries, the impact of socio‐economic status, and evaluation of benefits and costs of therapies. Techniques for improved clinical trial design were also studied.Pediatr Pulmonol. 2016;51:1251–1263. © 2016 Wiley Periodicals, Inc.